General Issues in International and European Law - Zyberi, Gentian (Utrecht Journal of International and European Law, 2015)
As a former editor of the predecessor to this journal, namely Merkourios, it gives me great pleasure to write the editorial for the 81st issue of the Utrecht Journal of International and European Law (“UJIEL”) on ‘General Issues in International and European Law’. After first providing a general overview of the materials contained in this issue, I will briefly highlight some of the main points made in, the five articles, the case note, two book reviews, and the interview.